Reconsidering Europeanization Ideas and Practices of (Dis-)Integrating Europe since the Nineteenth Century - Greiner, Florian 1981-; Pichler, Peter 1980-; Vermeiren, Jan ca. 20./21. Jh; Ziegerhofer, Anita 1965- (De Gruyter Oldenbourg, 2022)
This pertinent and highly original volume explores how ideas of Europe and processes of continental political, socio-economic, and cultural integration have been intertwined since the nineteenth century. Applying a wider definition of Europeanization in the sense of "becoming European", it will pay equal attention to counter-processes of disentanglement and disintegration that have accompanied, slowed down, or displaced such trends and developments. By focusing on the practices, agents, and experience of Europeanization, the volume strives to bring together the history of ideas and the history of human actions and conduct, two approaches that are usually treated separately in the field of European studies
Beiträge der Konferenz 'Europeanization, what else?! Ideas and practices since the 18th century' 13.-15.06.2019, Graz (Name/Daten ermittelt)
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Jul 2022)
War zeitweise als Open Access bei De Gruyter angezeigt. 28.6.22
Keywords: Geschichte 1800-2020; Desintegration; Europa; Europäisierung; Integration; HISTORY / Modern / General; Europäische Integration; Konferenzschrift -- 13.06.2019-15.06.2019 -- Graz